An Equilibrium Model of “Global Imbalances” and Low Interest Rates - Caballero, Ricardo J; Farhi, Emmanuel; Gourinchas, Pierre-Olivier (American Economic Review, 2008)
The sustained rise in US current account deficits, the stubborn decline in long-run real rates, and the rise in US assets in global portfolios appear as anomalies from the perspective of conventional models. This paper rationalizes these facts as an equilibrium outcome when different regions of the world differ in their capacity to generate financial assets from real investments. Extensions of the basic model generate exchange rate and foreign direct investment excess returns broadly consistent with the recent trends in these variables. The framework is flexible enough to shed light on a range of scenarios in a global equilibrium environment. (JEL: E44, F21, F31, F32)